UJI EFEKTIFITAS BEBERAPA JENIS ATRAKTAN UNTUK MENGENDALIKAN HAMA LALAT BUAH (Bactrocera dorsalis Hend.) PADA TANAMAN JAMBU BIJI (Psidium guajava L.) - Janter Simarmata Janter Simarmata; Yuswani Pangesti Ningsih; Fatimah Zahara (Jurnal Agroekoteknologi, 2013)
ABSTRACTEffectiveness Test of Several Types of Attractants for Controlling Fruit Flies Pest (Bactrocera dorsalisHendel) of Guava (Psidium guajava L.)". This research aims to determine the effectiveness of severaltypes of attractants to control fruit flies (Bractocera dorsalis Hendel) on Guava (Psidium guajava L.)in the field. This research using Randomized Block Design (RAK) non factorial with 5 treatments and5 replications are: A0 (Control), A1 (Attractant with Methyl Eugenol), A2 (Rongit Glue), A3 (LeilaGlue) and A4 (Clove oil extract + sugar). The results showed that Rongit glue, Methyl eugenolattractants, Leila glue, clove oil extract sugar effectively reduce the population of fruit flies(Bractrocera dorsalis Hendel) in the field. The highest result of trapped fruit flies is on treatment A2that is 130 and the lowest result is on treatment A0 (control) that is 0. In the sex ratio observations oftrapped fruit flies at any time. The highest is on observation I, males imago as many as 896 and femalesimago as many as 500, the lowest is on observation VIII, males imago as 255 and females 147.Keywords: guava, fruit flies, trap